Compostagem de resíduos sólidos de frigorífico - Costa, Mônica S. S. de M.; Costa, Luiz A. de M.; Decarli, Léo D.; Pelá, Adilson; Da Silva, César J.; Matter, Uilson F.; Olibone, Dácio [UNESP] (FapUNIFESP (SciELO), 2009)
Composting has been a viable and efficient alternative treatment to agroindustrial waste. This experiment was installed with the objective of analyzing the process of composting for slaughterhouse waste. Twelve piles of composting were prepared, using slaughterhouse waste, wheat straw and wood sawdust. The process was evaluated by daily temperature monitoring, observations of the occurrence of undesirable parameters (bad smell and/or ammoniacal smell, grease formation and presence of grubs and flies), as well as the capacity of recycling nutrients. The undesirable parameters were observed, on average, for the first five days after pile building; the temperatures increased, reaching 70 °C; chemical composition of compost showed relevant contents of macro and micronutrients, a high recycling potential. Utilization of impermeable floor and roof are recommended during the composting. The turning frequency used (15 days after pile building followed by turning) was adequate. The best relation of weight was 7.2 kg of waste for each kg of straw and 16.6 kg of waste for each kg of sawdust.
Composting of slaughterhouse solid waste
Keywords: Nutrients recycling; Temperature; Undesirable parameters; Triticum aestivum